2018
DOI: 10.5731/pdajpst.2017.008367
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Extractables Study of Autoclavable Polyethersulfone Filter Cartridges for Sterile Filtration

Abstract: Sterile filters are ubiquitous in biopharmaceutical manufacturing processes. Because such filters are in direct contact with the process fluid, profiling of the extractables is of utmost importance. The work presented here reveals the extractables profile from filter cartridges for sterilizing-grade filtration, which were obtained from six different vendors. All filters contain a 0.2 μm polyethersulfone membrane for sterile filtration combined with a polyethersulfone pre-filter with retention rates spanning fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… a Quantities estimated from UV signal using Tris(2,4‐di‐ tert ‐butylphenyl) phosphite as reference, degradants included methyl and ethyl esters for Irgafos® 168 or typical degradants after hydrolysis, oxidation, or tert ‐butyl split off for Irganox® 1010. 21 , 30 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Quantities estimated from UV signal using Tris(2,4‐di‐ tert ‐butylphenyl) phosphite as reference, degradants included methyl and ethyl esters for Irgafos® 168 or typical degradants after hydrolysis, oxidation, or tert ‐butyl split off for Irganox® 1010. 21 , 30 …”
Section: Resultsmentioning
confidence: 99%
“…The analytical system for analysis of the individual extractables, that is, GC‐MS and LC‐MS are qualified and used in routine extractables and leachables screening. Instrument parameters, the analytical methods, and the standard mixtures were identical to the conditions published by Menzel et al 30 Details about the instruments can be found in the Supporting Information S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Menzel et al recently published a comprehensive survey of extractables of current PES membrane filters. [ 8 ] PES oligomers were detected in extracts of the investigated filters by HPLC‐UV and LC‐HRMS analysis, but mass spectra were inconclusive. This urged us to examine these compounds further by obtaining a pure representative, elucidating its structure, and performing a toxicological evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Several cyclic oligomers can be expected to be present in PES polymers. [8,9] Though isolations and structures of cyclic oligomers from the very similar polymer polysulfone (PSU) are described in the literature, [10,11] a structural characterization of PES oligomers has not been reported. We only identified one reference that described the presence of PES oligomers in food contact materials (baby bottles).…”
mentioning
confidence: 99%